HISTOLOGICAL CHANGES IN THE LIVER OF GOBY FISHES INFECTED BY NEMATODES LARVAE EUSTRONGYLIDES EXISUS - Моргун, О. А.; Сорока, Н. М. (Scientific Progress & Innovations, 2017)
In the article we present histological changes in the liver of goby fishes infected by nematodes larvae Eustrongylides exisus. We found out a pathological process and structural changes in an organ that are characteristic for focal hepatitis. Hepatocytes are megascopic in a volume, rounded form, a kernel is pushed back to the shell of cell. Kernels are diminished in a volume, have wrong form (pyknosis). Kupfer’s cells are marked in some areas. Lymphoid-leukocytic infiltrations there are in liver parenchyma, perivascular and endovascular couplings. Kernels in hepatocytes are absent in the areas of cellular infiltrations. We marked that hepatocytes are presented by amorphous structureless mass. We found out excrescence of connecting tissue which is the protective reaction of organism in the presence of nematodes larvae Eustrongylides exisus in some places round cellular infiltrations.